2007
DOI: 10.1007/s00467-006-0414-x
|View full text |Cite
|
Sign up to set email alerts
|

Mesna or cysteine prevents chloroacetaldehyde-induced cell death of human proximal tubule cells

Abstract: Chloroacetaldehyde (CAA) is formed in the body from the chemotherapeutically used drug ifosfamide (IFO). CAA leads to cell death in proximal tubule cells mainly through the mechanism of necrosis rather than apoptosis. During chemotherapy, 2-mercaptosulfonic acid (mesna) is used with IFO to protect the urothel from cell damage. Little is known of the effect of mesna on renal proximal tubule cells, the primary site of damage after IFO treatment. Mesna contains a sulfhydryl (SH) group. To clarify whether SH-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…We also demonstrated that the nephrotoxic effects of 0.5 mM CAA were prevented by addition to the incubation medium of an equimolar concentration of mesna or a tenfold higher concentration of amifostine [12]. These results were confirmed by several studies conducted by other authors, showing that mesna and amifostine could prevent toxicity of CAA in vitro [30][31][32][33]. Despite the fact that the protecting concentration of thiols compounds were quite different among the various studies (from 200 to 800 μM), it must be emphasised that the protecting effect obtained under in vitro conditions was very efficacious and was promising to also prevent CAA toxicity in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…We also demonstrated that the nephrotoxic effects of 0.5 mM CAA were prevented by addition to the incubation medium of an equimolar concentration of mesna or a tenfold higher concentration of amifostine [12]. These results were confirmed by several studies conducted by other authors, showing that mesna and amifostine could prevent toxicity of CAA in vitro [30][31][32][33]. Despite the fact that the protecting concentration of thiols compounds were quite different among the various studies (from 200 to 800 μM), it must be emphasised that the protecting effect obtained under in vitro conditions was very efficacious and was promising to also prevent CAA toxicity in clinical practice.…”
Section: Discussionsupporting
confidence: 87%
“…The mechanism of such cell death follows the apoptotic cell death (Takahashi et al, 2007), although necrotic mechanism of cell death has also been mentioned by other workers (Daniel et al, 1992). Infiltration of inflammatory leucocytes which already use to accompany necrosis (Schwerdt et al, 2007;Chen et al, 2008) was seen in the present study. The fatty changes or liver steatosis caused by using IFO stored at 10 and 25°C may be related to changes in the chemical structure of the drug due to storing temperature.…”
Section: Discussionsupporting
confidence: 85%
“…3 2-mercaptoethane sulfonate (mesna) is a small, synthetic, highly water-soluble molecule that has the potential to scavenge reactive oxygen species by virtue of its sulfhydryl group. 6 It is principally used to reduce the hemorrhagic cystitis induced by cyclophosphamide and ifosfamide, but it is also widely used as a protective agent against chemotherapy toxicity. To the best of our knowledge, there have been no previous investigations of whether mesna ameliorates neuronal injury and neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%